ANALYSIS OF MORAL AND CULTURAL VALUES IN THE HUNGER GAMES BY SUZANNE COLLINS - Bagiono, Felicia Nathania; Meidasari, Venny Eka; Martiarini, Elyza (Universitas Indraprasta PGRI, 2024)
Film is one of the media frequently used by many people. This research aims to utilize films as a learning medium for students who want to understand foreign cultures, gain advanced literacy skills in English, and learn correct pronunciation. The Hunger Games by Suzanne Collins contains moral messages and cultural values. In this research, the author discusses the moral messages according to Suseno's theory and the cultural values according to Koentjaraningrat's theory contained in the film, and analyzes them using a qualitative descriptive method by explaining data derived from film excerpts.